The Influence of Good Corporate Governance, Corporate Social Responsibility, and Financial Literacy Principles on the Financial Performance of Village Credit Institutions in the Negara District of Jembrana - Komang Ayu Nadya Suhita Lestari; Etty Puji Lestari; Sri Astuty (International Journal of Applied Business and International Management, 2024)
This research aims to analyze the influence of good corporate governance, corporate social responsibility, and financial literacy on financial performance in Village Credit Institutions in Negara District, Jembrana Regency. There are 3 independent variables and 1 dependent variable. GCG, CSR, and financial literacy variables are included in the dependent variables and the financial performance variables are included in the dependent variable. To answer the problem formulation, quantitative analysis was used using an instrument in the form of a questionnaire. In this research, the SPSS 25 application was used to analyze these variables. Based on the result of the analysis, it can be concluded that: 1. GCG variables partially have a significant effect on financial performance (0.0170.05) 2. The CSR variable partially has a significant effect on financial performance (0.0000.05) 3. The financial literacy variable partially does not have a significant effect on financial performance (0.338 0.05) 4. GCG, CSR and financial literacy variables simultaneously influence financial performance (0.0000.05).